Governing women's morality: a study of Islamic veiling in Canada - Atasoy, Y. (EUROPEAN JOURNAL OF CULTURAL STUDIES, 2006)
The veiling of Muslim women is subject to strongly contested ideas about whether the veil is a symbol of women's subordination to an oppressive tradition or a means of emancipation from that tradition. This article suggests that women's own personal reasons for veiling must be analysed. Data collected from published documents from Muslim organizations allows for demonstration that the veil is configured as central to an Islamic moral code of female modesty. A further analysis of findings from interviews conducted with veiled Muslim women in Winnipeg shows the nuanced ways in which women enact this code.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; corps; cours; discipline; féminisme islamique; histoire et politique; identité; manitoba; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; winnipeg

Corps, sexe et art: dimension symbolique - Pearl, Lydie (L'Harmattan, 2001)
Les années 60 marquent le début d'un art éphémère dans lequel l'objet d'art disparaît au profit d'une mise en scène du corps. Les Actionnistes viennois mêlent des corps féminins ou masculins dans la boue, du sang et des organes animaux etc. Comment ce qui peut paraître aberration ou perturbation de la personnalité est souvent une mise en scène microcosmique des idéologies ou des réalités politiques d'une époque : images d'une coupure Est/Ouest, de frontières infranchissables à l'époque de la guerre froide ou, au contraire, effacement des frontières au temps de la mondialisation avec des artistes de la Scène internationales
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; anthropologie; approches et analyses; art contemporain; arts; corps; cours; discipline; har4600; histoire de l'art; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sexualité; thématiques